Finite element simulation analysis of flow heat transfer behavior and molten pool characteristics during 0Cr16Ni5Mo1 laser cladding - Wen-Lin Ye; Ai-Dong Sun; Wen-Zheng Zhai; Gui-Lan Wang; Chun-Ping Yan (Journal of Materials Research and Technology, 2024)
0Cr16Ni5Mo1 super martensitic stainless steel has excellent weldability and is an economical material with a high life cycle and low cost, but there are few researches and applications of this material in additive manufacturing. In order to realize the application of 0Cr16Ni5Mo1 large-area laser cladding technology, the multi-track lap cladding of the material was studied. In this work, a multi-physical finite element model of multi-layer multi-track laser cladding was established, taking into account thermodynamic processes such as phase transition, Marangoni convection, and buoyancy. The flow and heat transfer behavior of 0Cr16Ni5Mo1 in multi-layer multi-track laser cladding process and the characteristics of the molten pool are studied. The research focused on the flow heat transfer behavior and molten pool characteristics of 0Cr16Ni5Mo1 during multi-layer multi-track laser cladding. The discussed aspects include the evolution history of the temperature field within the molten pool, flow field characteristics, molten pool dimensions, and dilution ratio under various laser powers and overlap rates. The results show that with the increase of overlap rate, the morphology of molten pools in different clad tracks will also change, and the flow rate, dilution ratio, and length of molten pools in the second track are negatively correlated, while the temperature and height of molten pools are positively correlated. As the laser power increases, all the characteristic quantities are positively correlated with it.